Do prognosis and clinicopathological features differ in young early-stage breast cancer? - Arikan, Akif Enes; Kara, Halil; Dülgeroğlu, Onur; Erdoğan, Esin Nur; Capkinoglu, Emir; Uras, Cihan (Frontiers in Surgery, 2022)
Background: Breast cancer is the most frequently detected cancer and the leading cause of cancer-related death in women. Although it is mostly seen in older patients, breast cancer affects women aged 24 to >70 years, with poorer prognosis in young patients. Young age remains a controversial topic in the literature. This study aimed to identify subtype differences and the effect of age on early-stage breast cancer outcomes. Methods: A total of 300 consecutive patients underwent surgery between 2011 and 2015 for early-stage breast cancer. Of these, 248 were eligible for this study and were divided into three groups. group Y (aged ≤35 years ), group M (aged >35 and ≤45 years), and group E (aged >45 years). The clinical and pathological features and data related to recurrence, metastasis, and death were recorded. Results: No statistical differences were found between groups regarding histopathological features except for higher histological grade and Ki-67 levels in group M. Additionally, group Y recorded no progression (recurrence or metastasis) or death. Disease-free survival was 117.8 months (95% CI 111.8–123.8) for group M, which was significantly shorter than that for group E (p<0.001). Additionally, the hazard ratio (HR) for progression from group M to group E was 10.21 with significant difference (p=0.003, 95% CI 2.26–46.08). However, the HR of group Y to group E was 0.04, without significance (p=0.788, 95% CI 0.18–345 ×106). The overall 5-year survival was 100% in group Y, 98.8% in group M, and 99.3% in group E, without significance. Conclusion: A very young age cannot be considered an independent risk factor for poor prognosis. Rather than age, histological grade and Ki-67 index are more important factors in early-stage breast cancer.